A review of Ochosternus Candèze, 1863 from Lord Howe Island, Australia and key to the genera of Elateridae occuring there (Coleoptera: Elateridae: Elaterinae) - Rosas, Matilda. L.; Chan, Cynthia; Reid, Chris. A. M. (Zootaxa, 2025)
The genus Ochosternus Candèze, 1863 is revised for Lord Howe Island, with three species: O. howensis Lea, 1929, O. goodyeri new species and O. huttoni new species. The definition of Ochosternus is discussed in relation to similar Elaterinae in the region. An exotic pasture pest, Monocrepidius exsul Sharp, 1877, is noted as well-established on the island. Keys are provided for identification of the Ochosternus species and for the seven elaterid genera on Lord Howe Island.